Examining death loss in Kansas feedlots - A. Babcock; R. Jones; Michael R. Langemeier (Kansas Agricultural Experiment Station Research Reports, 2006)
This study had three primary objectives: 1) to determine if there is an annual and/or seasonal trend in percentage of death loss in Kansas feedlots; 2) to examine the difference in death loss between steers and heifers; and 3) to evaluate if "in" weight has had an effect on percentage of death loss in Kansas feedlots. The annual trend in death loss for both steers and heifers was found to be significant and positive, indicating that death loss has been increasing over the sample period. Seasonal increases in death loss were significant for early-spring closeouts for both steers and heifers. The annual trend in the difference between the death loss for steers and heifers, though not significant, was negative. There were, however, certain closeout months in which there were significant differences in the death loss of steers relative to heifers. Placement weight had a significant negative impact on death loss in heifer finishing, but no significant impact on steer finishing. Our regression analysis indicates that death loss has been increasing over the sample period, that certain closeout months tend to impact steer and heifer death loss differently, and that placement weight in heifers has had a significant impact on percentage of death loss in cattle.
Keywords: Cattlemen& #x27; s Day; 2006; Kansas Agricultural Experiment Station contribution; no. 06-205-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 959; Beef; Death loss; Feedlots